The Relevance Of Globalization And The Literary Process - Nizamova Feruza Alimullaevna (Genius Journals, 2024)
The article says that globalization, being one of the dominant trends of modern civilization, has an extremely strong impact not only on socio-economic and political, but also on the cultural aspects of society, in particular, literature. The author pays special attention to the consideration of the main aspects of the ambiguous impact of globalization and information technology on the literary process.
Keywords: Literary Process; Globalization; Information Technologies